Tinjauan Hukum Islam tentang Tradisi Mabbollo dalam Adat Perkawinan Bugis (Studi Kasus di Kelurahan Biru Kecamatan Tanete Riattang Kabupaten Bone) - Amir, Amirullah (STAI YAPIS Takalar, 2024)
The reality is that in Biru sub-district it is still debated because there are people who still adhere to customary law which believes that if the younger sibling steps over their older sibling in marriage, then it is feared that the older sibling will find their soul mate in a very long time and in addition there will be a disaster that will happen to them. when stepping over a sibling. In the community environment in the Biru sub-district that the author studied, the author saw that the custom of giving money as a stepper is still strongly in force, that is, if there is a marriage, stepping over the older sibling and if there is a younger brother who gets married by stepping over his older brother or vice versa. So it is believed that a disaster will befall the family if the traditional ceremony of giving money is not carried out first. In marriage customs in the Biru Village community, there is a custom that if someone wants to get married but there is an older sibling who is not married, then that person must wait for their older sibling to get married first, so many people consider it sacred not to carry out a procession of giving money or goods as a step/gift.